2022
DOI: 10.3390/cancers14133102
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inhibition of FOSL-1 and YAP Using siRNA-Lipoplexes Reduces the Growth of Pancreatic Tumor

Abstract: Pancreatic cancer evades most of the current therapies and there is an urgent need for new treatments that could efficiently eliminate this aggressive tumor, such as the blocking of routes driving cell proliferation. In this work, we propose the use of small interfering RNA (siRNA) to inhibit the combined expression of FOSL-1 and YAP, two signaling proteins related with tumor cell proliferation and survival. To improve the efficacy of cell transfection, DODAB:MO (1:2) liposomes were used as siRNA nanocarriers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“… 157 DODAB: MO (1:2) liposomes were employed as siRNA-lipid complexes prepared by siRNA nano-carriers, which could target FOSL-1 and YAP, leading to significant restrain of tumor growth. 158 Experiments revealed that the AuNRs complex could regulate the release of drugs under 665 nm light treatment, and exhibit synergistic antitumor effects when co-delivering siRNA and adriamycin based on gold nanorods. 159 A novel delivery system for gemcitabine and miR-21 inhibitors, based on dendritic-embedded gold nanoparticles and ultrasonic targeted microbubble destruction (UTMD) technology, showed great potential in the treatment of pancreatic cancer.…”
Section: Combined Administration Strategy For Pancreatic Cancermentioning
confidence: 99%
“… 157 DODAB: MO (1:2) liposomes were employed as siRNA-lipid complexes prepared by siRNA nano-carriers, which could target FOSL-1 and YAP, leading to significant restrain of tumor growth. 158 Experiments revealed that the AuNRs complex could regulate the release of drugs under 665 nm light treatment, and exhibit synergistic antitumor effects when co-delivering siRNA and adriamycin based on gold nanorods. 159 A novel delivery system for gemcitabine and miR-21 inhibitors, based on dendritic-embedded gold nanoparticles and ultrasonic targeted microbubble destruction (UTMD) technology, showed great potential in the treatment of pancreatic cancer.…”
Section: Combined Administration Strategy For Pancreatic Cancermentioning
confidence: 99%
“…242 In other ways, sequential administration of cell-cycle kinases CDK4 and CDK6 inhibitors after taxane treatment reduced cell proliferation in PDAC mouse model with both KRAS G12V and Cdkn2a-null mutations. 243 Diego-González et al 244 found that lipoplexes of si-FOSL-1 and si-YAP reduce the tumor growth in mice carrying tumors induced by pancreatic tumoral cell lines (KRAS G12V and p53 knockout) through peri-tumoral injection.…”
Section: Therapy Of Pc With Kras G12vmentioning
confidence: 99%
“… 243 Diego‐González et al. 244 found that lipoplexes of si‐FOSL‐1 and si‐YAP reduce the tumor growth in mice carrying tumors induced by pancreatic tumoral cell lines (KRAS G12V and p53 knockout) through peri‐tumoral injection.…”
Section: Combination Strategies Adapted To Specific Mutations In Diff...mentioning
confidence: 99%